Relationship Between Firm Resources and Product Innovation Performance in Malaysian Small Medium Enterprises: The Moderating Role of Age & Size - Lily Julienti, Abu Bakar (2011)
The purpose of this research was to assess the product innovation performance (PIP) in small and medium-sized enterprises (SMEs) in the Malaysian manufacturing sector. The research focused on SMEs because of the high percentage of them in the Malaysian business population. Furthermore, manufacturing SMEs are mostly involved in innovation activities. Also, there are increasing levels of product innovation in the manufacturing sector in recent years. The present research has assessed the actual and expected relationship of the resources of SMEs and PIP. It has also discussed the moderation effect of the size and age of the SME on this relationship. In addition, there are also findings on the most innovative manufacturing industries in Malaysia. This research uses survey methodology that includes a descriptive analysis, test of non-response bias, validity and reliability analysis and regression analysis (multiple and hierarchical) of the study population from among SMEs in the manufacturing sector. Findings showed that the production of electrical and electronic industry (E&E) has achieved the highest PIP. In terms of the direct relationship between SME resources and PIP, the results showed no relationship between tangible resources and PIP. On the other hand, intangible resources demonstrated a positive relationship with PIP. Moreover, there was a partial moderation effect of the SME’s age towards SME tangible resources and PIP. Conversely, the size if an SME does not moderate the relationship between SME resources and PIP. Originality of this study is to contribute to the flow of resource view (RBV) and innovation research, especially in the context of the study, conceptualization and methodology. In terms of the direct relationship between SME resources and PIP, the results showed no relationship between tangible resources and PIP. On the other hand, intangible resources demonstrated a positive relationship with PIP. Moreover, there was a partial moderation effect of the SME's age towards SME tangible resources and PIP. Conversely, the size if an SME does not moderate the relationship between SME resources and PIP. Originality of this study is to contribute to the flow of resource view (RBV) and innovation research, especially in the context of the study, conceptualization and methodology. The findings of this research also provide important contributions for practitioners and policy-makers in developing policies and strategies for promoting SMEs.